PENERAPAN MEDIA PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENULIS IKLAN KELAS V PESERTA DIDIK SDIT IQRA KOTA SERANG - Delviana Aulia, Dhena; Hilaliyah, Tatu; Jamaludin , Ujang (ATTA`DIB, 2025)
Application of Learning Media and Learning Motivation to Class V Advertisement Writing Skills of SDIT IQRA Serang City Students. The background of this research is to determine the application of learning media and learning motivation to advertising writing skills. The objectives of this research are (1) To determine the differences in advertising writing skills of students using leaflet learning media and Canva learning media (2) To determine the differences in advertising writing skills of students who have high learning motivation and low learning motivation (3) To determine interactions between the application of learning media and learning motivation on students' advertising writing skills (4) To determine the differences in advertising writing skills of students who use leaflet learning media and Canva learning media in groups of students who have high learning motivation (5) To determine the differences in writing skills advertisements for students who use leaflet learning media and Canva learning media in the group of students who have low learning motivation (6) To determine the difference in advertising writing skills of students who have high motivation and those who have low learning motivation in the group of students who use leaflet learning media (7) To determine the difference in advertising writing skills of students who have high motivation and those who have low learning motivation in the group of students who use the Canva learning media. A learning media is needed that can increase students' motivation in the learning process, especially in learning advertising materials. Students can write advertisements for traditional specialties from vocabulary arranged into sentences. In realizing this activity, of course, the application of learning media and learning motivation is carried out, because to get good and maximum results it is necessary to get appropriate material to support learning. The method used in this research is experimental research. The type and source of data used is quantitative data, this research was conducted on class V students at SDIT IQRA Koa Serang. Data collection techniques using questionnaires and tests. The sig value of equal variances nor assumed > 0.05 means that H0 is accepted and H1 is accepted and it can be stated that the data comes from a population that has the same variance. It can be concluded that there are differences in the advertising writing skills of SDIT IQRA students who have high learning motivation and low learning motivation in students who use the Canva learning media.